Year-round itinerary of a GPS-tracked Brent Goose Branta b. bernicla that visited the Bassin d’Arcachon, France - Dokter, Adriaan M.; Ebbinge, Barwolt S. (Wildfowl, 2013)
The year-round itinerary for a Dark-bellied Brent Goose Branta b. bernicla is describedÂ for a bird fitted with a GPS tracking device at Terschelling Island, the Netherlands, inÂ spring 2012. Spring migration commenced when the bird left the Dutch Wadden SeaÂ on 27 May and continued until it reached the Taimyr Peninsula in arctic Russia on 8Â June. During the summer months it moved along the coast of the Taimyr Peninsula,Â prior to moulting on Taimyr Island to the north of the peninsula in July. During autumnÂ migration it frequented eelgrass Zostera sp. beds around Langeness Island in Schleswig-Holstein, Germany and then proceeded to the Bassin dâ€™Arcachon in France, anotherÂ famous eelgrass area, where it remained from 18 October 2012â€“12 January 2013 beforeÂ returning to feed on grassland polders on Terschelling Island in January 2013. TheÂ timing of the location data showed that the bird flew large distances in short periods ofÂ time during migration. Over the year it covered c. 4,600 km during local movements andÂ c. 15,000 km on migration. The results form part of a larger study investigating theÂ importance of non-breeding habitats (particularly eelgrass vegetation) for the species.